Semi-Official Hungarian Efforts in the United States for Territorial Revision in the 1920s - Mathey, Éva (AMERICANA E-journal of American Studies in Hungary, 2020)
The revision of the Treaty of Trianon and, thus, the rectification of Hungary’s post-World War I borders were important national concerns for Hungarians during the interwar period—a program which had to be implemented rather cautiously, given Hungary’s fragile international status after the Great War. Trianon generated a great amount of Hungarian propaganda concerning territorial revision for domestic as well as international circulation with the purpose to expose the adverse consequences of the treaty, explain its injustices, generate a positive image of the country, and ultimately win support for revision. Since the possibilities of official, governmental revisionism were rather limited until after the second half of the 1920s, revisionism found new, semi-official channels. Notwithstanding the fact that Hungarian revisionist policies and propaganda were mostly directed toward Western European countries, especially during the 1920s, Hungarians also targeted the United States, the country of fair play and democracy, which—reinforced by a variety of often misconceived political, historical, and cultural tenets—was considered by Hungarians as a potential ally in their efforts to revise the Trianon borders. This essay presents some important mainstream, non-governmental, yet front-line contributions to revisionist propaganda aimed at the United States, such as the efforts of Counts István Bethlen, Pál Teleki and Albert Apponyi to present the nature of such revisionist endeavors and explain why such revisionist hopes were unfounded.